ANALISIS KADAR HDL PADA PEROKOK AKTIF USIA 31-35 TAHUN DI KELURAHAN KEMAYORAN BANGKALAN - Yogi Khoirul Abror; Devi Anggraini Putri (NHM PRESS, 2021)
Smoking is one of the health problems that is difficult to solve even has become a national and international problem. One of the negative effects of smoking is a decrease in HDL levels in the body. The purpose of this study was to determine the description of HDL levels in active adult smokers aged 31-35 years in RT.04 / RW.01 Mlajah Bangkalan Village. This research is a descriptive study, with a research design using cross sectional design. The variable of this study is the level of HDL in active smokers with a population of 15 respondents selected as samples using total sampling. The data collection method uses a photometer, the data obtained are then presented in a frequency distribution table. The results of research on HDL levels of active smokers mostly low HDL levels less than 60 mg / dl with 11 respondents (73.33%) .This happens because the nicotine contained in cigarette smoke will stimulate the hormone adrenaline which will consequently interfere with fat metabolism which causes HDL levels in the body decrease.